2022
DOI: 10.1609/aaai.v36i3.20268
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Single-Modal Optical Flow Network for Diverse Cross-Modal Flow Estimation

Abstract: In recent years, optical flow methods develop rapidly, achieving unprecedented high performance. Most of the methods only consider single-modal optical flow under the well-known brightness-constancy assumption. However, in many application systems, images of different modalities need to be aligned, which demands to estimate cross-modal flow between the cross-modal image pairs. A lot of cross-modal matching methods are designed for some specific cross-modal scenarios. We argue that the prior knowledge of the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The objective here is to assess the impact of incorporating video frames as conditioning signals in additional to text. For the task of dance-to-music generation, we further compare V2Meow with baseline models D2M-GAN (Zhu et al 2022a), CDCD Step-Intra (Zhu et al 2022b), and CMT (Di et al 2021) on the AIST++ test split, aiming to evaluate V2Meow's understanding of complex dance motion. Detailed results are presented in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The objective here is to assess the impact of incorporating video frames as conditioning signals in additional to text. For the task of dance-to-music generation, we further compare V2Meow with baseline models D2M-GAN (Zhu et al 2022a), CDCD Step-Intra (Zhu et al 2022b), and CMT (Di et al 2021) on the AIST++ test split, aiming to evaluate V2Meow's understanding of complex dance motion. Detailed results are presented in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the field made significant progress when RAFT (Teed and Deng 2020) proposed a new recurrent optical flow network to estimate optical flow. Based on this breakthrough architecture, many recurrent networks (Jiang et al 2021b;Luo et al 2022b;Sui et al 2022;Xu et al 2021;Zhang et al 2021;Zheng et al 2022;Zhou et al 2023) have been proposed. For example, GMA (Jiang et al 2021a) suggested combining global motion to solve the problem of estimating occlusion, and KPA-Flow (Luo et al 2022a) designed kernel patch attention to deal with the local relationships of optical flow.…”
Section: Related Workmentioning
confidence: 99%
“…Being popular in self-supervised learning, contrastive learning (CL) allows models to learn the knowledge behind data without explicit labels (Xia et al 2022;Zhu et al 2023). It aims to bring an anchor (i.e., data sample) closer to a positive/similar instance and away from many negative/dissimilar instances, by optimizing their mutual information in the embedding space.…”
Section: Contrastive Learningmentioning
confidence: 99%